Quantifying the services of natural and built infrastructure in the context of climate change: the case of the Tana River Basin, Kenya - McCartney, Matthew P.; Foudi, S.; Muthuwatta, Lal P.; Sood, Aditya; Simons, G.; Hunink, J.; Vercruysse, K.; Omuombo, C. (International Water Management Institute, 2019)
This report presents findings from a study conducted to explore the synergies and trade-offs between built (i.e., engineered) and natural (i.e., ecological systems) infrastructure in the Tana River Basin, Kenya. The study considered hydrological, ecological and economic processes in order to value flow-related ecosystem services. It provides quantitative insights into the links between flow and the benefits derived from both built and natural infrastructure. The results provide initial perspectives not just on the monetary values of a number of ecosystem services (and how they change as flows vary and are altered by large dams) but also, importantly, aspects of equity and social inclusion, that also need to be considered in decision-making.